Peripartum hysterectomy for cesarean section with morbidly adherent placenta: case series of 25 patients - Rageh, Abdulrahman M.; Khalaf, Mohamed; Abbas, Ahmed M.; Salem, Hossam T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The current paper reports the outcome of case series of patients presented with placenta accreta confirmed histopathologicaly after management by peripartum hysterectomy. Methods: The study was set in Women’s Health Hospital, Assiut University, Egypt. This was a case series of 25 women presented with placenta accreta between May 2017 and April 2018. We included all pregnant women with placenta previa as diagnosed by ultrasound with suspicion of abnormal placentation by Doppler, confirmed intra-operatively undergoing either emergent or elective CS. All cases were performed by an expert team of obstetricians and anesthetists. Cesarean delivery was done under general anesthesia through pfannensteil incision. The primary outcome was the estimated intra-operative blood loss through assessment of amount of blood in the suction by ml, difference between the weight of surgical drapes and towels before and after operation. Results: Pre-operative Hb was 10.64±1.01 gm/dL and there was significant decline in the postoperative Hb reaching 8.36±1.21 gm/dL (p<0.001). The mean drop in Hb was 2.28±1.43gm/dL. Estimated intra-operative blood loss was 974.4±398.05 ml in the towels and 847.6±362.56 ml in the suction apparatus. The total blood loss was 1822±653.73 ml. The mean number of units of whole blood transfused was 2160.0±825.6 ml and fresh frozen plasma was 1010.0±349.7 ml. Regarding intra-operative complications, bladder injury was the most common one in 14 cases (56%), followed by ureteric injury in two cases (8%). Postoperative ICU admission was in 6 cases (24%) and the mean duration of hospital stay 12.44 ± 4.07 days. No cases of maternal mortality. Conclusions: In conclusion, peripartum hysterectomy is considered life-saving surgery in patients with placenta accreta.